Private Sector in Indian Healthcare Delivery: Consumer Perspective and Government Policies to promote private Sector - Shah, Utkarsh (Information Management and Business Review, 2010)
This research paper attempts to collate literature from various sources, in an attempt to answer three pertinent questions related to healthcare in India. Firstly, what is it meant by ‘private sector’ in healthcare delivery system of India, secondly how has the private sector evolved over the decades and what has been the role of the government in propelling the growth. Finally, the paper tries to highlight some of the factors that have promoted the growth of private sector in India with specific reference to quality of medical care. The paper explicitly indicates that the deficiencies in the public health delivery system of India, was the key to growth of private infrastructure in healthcare. The shift of hospital industry for ‘welfare orientation’ to ‘business orientation’ was marked by the advent of corporate hospitals, supported by various policy level initiatives made by the government. Today, there are over 20 international healthcare brands in India with several corporate hospitals. However, a large section of the ‘private healthcare delivery segment’ is scattered and quality of medical care continues to remain a matter of concern. This paper tracks the various government initiatives to promote private investment in healthcare and attempts to explore the reasons for preference of the private sector. Surprisingly, in contrast to contemporary belief, quality of medical care doesn’t seem to be the leading cause for preference of the private sector. Except for a few select corporate and trust hospitals, quality of medical care in private sector seems to be poor and at times compromised.